Comparative Study of Histopathological and Immunohistochemical Features of Biopsies of Patients of Lung Cancer - Sadia Islam, Ayesha Anwar, Shamila Tahir, Asma Kazi, Aisha Aziz, Hassan Farooq (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: When it comes to pollution, smoking, infections, tuberculosis (TB), and allergies, the lungs are the most sensitive organs to damage. Pleural fluid is a fluid that fills the parietal and visceral layers of the pleura that surround the lungs and helps to keep them moist. An investigation of the link between age, gender, and immunohistochemistry findings in lung and pleural biopsy samples was conducted. Materials and procedures: This is a four-year retrospective study that will take place between May 2017 and May 2021. In the current study, a total of 112 cases were submitted for histological investigation, with 100 instances using lung biopsy and 12 cases involving pleural biopsy being the most prevalent. Immunohistochemical testing was carried out as and when it was necessary. Results: A total of 100 lungs were examined. There were 56 cases of neoplastic tumours, 35 cases of non-neoplastic tumours, and nine cases of inconclusive tumours. The most common type of cancer was squamous cell carcinoma. The most prevalent non-neoplastic lesion was angioedema, which was the most common type of lesion (4 percent ). Patients with lung tumours who have malignancy outweigh those who have inflammatory illnesses at our institution. Seven of the 11 pleural biopsy cases were malignant, whereas the other eleven were not. Adenocarcinoma was the most common kind of neoplastic pleural lesion, followed by tuberculosis. Conclusion: The use of histopathology in the diagnosis of lung and pleural lesions is essential. It is possible to increase the accuracy of histological diagnosis with the use of immunohistochemistry.